Complex unloading behavior of titanium alloy in cold and thermal-mechanical working. (1st November 2022) - Ma, J.; Li, H.; He, Z.R.; Yang, H.; Fu, M.W.
Highlights: Strain-/temperature-dependent nonlinear unloading behavior of titanium alloy in thermal-mechanical deformation is experimentally characterized. Unloading nonlinearity in terms of modulus reduction effect and nonlinear stress-strain response is weakened with the increase of forming temperature. A physically-based model is developed for the prediction of the temperature-dependent evolution of strain-related nonlinear modulus degradation. Dynamic evolutions of reversible mobile dislocation density and mean free path account for the mechanism of complex nonlinear unloading behavior under thermal-mechanical working. Abstract: Unloading behavior is of crucial importance in metal forming, which particularly creates challenges for springback analysis and control of shape and dimensional accuracies of the manufactured components. For the working with hard-to-form materials at elevated temperatures, the thermal-mechanical coupling effect makes the unloading process more complicated and thus more difficult to model and control. Establishing an insight into the thermal-mechanical unloading behavior is crucial for ultimately improving the shape and dimensional accuracy of formed components. In this research, by using a near-alpha high-strength titanium alloy as a case study material, a series of continuous loading-unloading-reloading experiments within cold and warm forming domains were designed and conducted. Through the experiments, the complex unloading behavior, specially for the temperature-dependent degradation effect of elastic modulus and nonlinear stress-strain response, was investigated. A physically-based model was developed to reproduce the temperature-dependent nonlinear reduction effect of elastic modulus. In this model, the reversible mobile dislocation density is particularly included and represented to describe the evolving nonlinear elastic strain component upon unloading affected by both plastic strain and deformation temperature. Based on the model-based analysis, the mechanism accounting for the complex unloading nonlinearity in thermal-mechanical working was discussed and revealed from different evolutions of dislocation behaviors depending on plastic deformation and temperature. Graphical abstract: Image, graphical abstract